Ab initio study of impact of nitridation at amorphous-SiNx/GaN interface. (12th July 2018) - Zhang, Zhaofu; Hua, Mengyuan; He, Jiabei; Tang, Gaofei; Qian, Qingkai; Chen, Kevin J.
Abstract: A set of amorphous-SiN x /GaN interfaces is studied by ab initio calculation to understand the effects of GaN surface nitridation on interface state distribution. This study reveals that for the Si-rich SiN x /GaN interface without nitridation, both shallow and deep traps exist in a wide energy range within the GaN bandgap. However, with proper surface nitridation prior to SiN x deposition, the interface exhibits a much cleaner bandgap structure with significantly suppressed interface state density ( D it ). With the increase in the interfacial N-adatom coverage ratio, the shallow traps dramatically disappear while the deep traps merge into the GaN valence band, indicating a high-quality interface with low D it after sufficient nitridation. The low D it would eventually lead to enhanced V th stability in GaN metal–insulator–semiconductor (MIS)-gate devices. The nitridation effects on D it are further verified by capacitance–voltage ( C – V ) measurements in the GaN metal–insulator–semiconductor (MIS) diode with/without interface nitridation.